Subsystem identification in structures with a human occupant based on composite frequency response functions. (1st April 2019) - Wei, Xiaojun; Živanović, Stana; Russell, Justin; Mottershead, John E.
Highlights: A method for the subsystem identification in a human-structure system is proposed. It enables the subsystem dynamic identification from measured composite FRFs. The method is simple in problem formulation and economical in implementation. It is applicable to the correction of the operator effects in impact hammer testing. Abstract: A method is proposed for the subsystem identification of a composite system composing a lightweight low-frequency civil engineering structure and a human occupant. It is shown for the first time that the dynamics of the structure and the stiffness and damping of the human occupant can be determined from the frequency response functions of the composite system and the known mass of the human occupant. The advantage of the proposed approach over existing methods is not only in the simplicity of problem formulation but also in the substantial reduction of experimental complexity. Subsystem identification is demonstrated using a numerical example and two experimental case studies. In the first experimental case study, the method is applied to a laboratory bridge with a human occupant in a standing posture and frequency response functions are measured using shaker testing. In the second case study, the method is applied to a laboratory bridge with a hammer operator crouching on the bridge to perform impact hammer tests. It is demonstrated that subsystem dynamics can be accurately identified. The method is especially applicable to the correction of the effect of the hammer operator in manually operated impact hammer testing. In addition, the method can be generalised for the compenstation of the effects of the electrodynamic shaker in shaker testing for civil engineering applications.